Kant and the problem of morality : rethinking the contemporary world - Caranti, Luigi; Pinzani, Alessandro (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book examines the significance of Kant's moral philosophy in contemporary philosophical debates. It argues that Kant's philosophy can still serve as a guide to navigate the turbulence of a globalized world in which we are faced by an imprescriptible social reality wherein moral values and ethical life models are becoming increasingly unstable. The volume draws on Kantian ethics to discuss various contemporary issues including sustainable development, moral enhancement, sexism, and racism. It also tackles general concepts of practical philosophy such as lying, the different kinds of moral duties, and the kind of motivation one needs for doing what we consider to be the right thing. Featuring readings by well-known Kant specialists and emerging scholars with unorthodox approaches to Kant's philosophy, the volume will be of great interest to scholars and researchers of philosophy, politics and ethics. It will also appeal to moral theorists, applied ethicists and environmental theorists"--
Includes bibliographical references and index.
Keywords: Kant, Immanuel, -- 1724-1804.; Ethics